Lloyd Fernando (31 May 1926 - 28 February 2008) - Quayum, Mohammad Abdul (Gale Cengage, 2009)
An essay on the life and works of Lloyd Fernando, a Malaysian writer, who is often credited with the first Malaysian novel in the English language, Scorpion Orchid, published in 1976. The article examines Fernando's contributions to Malaysian literature and his overall significance as one of the pioneering figures in the field.